Peran Orang Tua dalam Pembelajaran Daring Anak Usia 5-6 Tahun Selama Masa Pandemi Covid-19 Di Kelurahan Mataram Barat Kecamatan Selaparang Tahun 2021 - Ni Wayan Dera Sukerani; Muazar Habibi; Ika Rachmayani; I Nyoman Suarta (Indonesian Journal of Elementary and Childhood Education, 2022)
The background of the problem from this research is the Covid-19 pandemic which requires schools to hold online learning that requires the role of parents. The purpose of this study was to determine the forms of parental roles in children's online learning activities and how parents apply forms of guidance to children when learning online during the Covid-19 pandemic in West Mataram Village, Selaparang District. The type of research used is descriptive qualitative. The data sources for this study were 4 parents with children aged 5-6 years who took online learning during the Covid-19 pandemic in the West Mataram Village, Selaparang District in 2021. Data collection methods used are observation, interviews, and documentation. Data analysis used the Miles and Huberman model. The technique of validating the research data includes credibility test, transferability test, dependability test and confirmability test. The results showed that the role of parents in online learning for early childhood during the COVID-19 pandemic was parents as educators, motivators, facilitators, mentors. The application of the forms of parental roles in online learning during the Covid-19 pandemic in the West Mataram Village, Selaparang Sub-district was very good with the average score achieved by the 4 research subjects was 91.65%. From this study it can be concluded that the role of parents in online learning for children aged 5-6 years in the West Mataram Village, Selaparang District in 2021 is very good, parents have played their role in educating, guiding, helping, and facilitating the needs of children at home.